Implementation of Discharge Planning, Home Care, Knowledge Level And Independence In Mother Postpartum primiparous - Dina Indrati; Dyah Sulistyowati; Hartati Hartati; Ratifah Ratifah (Jurnal Riset Kesehatan, 2012)
The objective of the study is to evaluate the levels of knowledge and self care in mothers with the primipara post partum in Purwokerto before and after intervention both control and experimental group. Quasi-experimental two group design was applied in the study. Forty eight mothers with primipara post partum were recruited from Prof. dr. Margono Soekarjo hospital and maternal clinic in Purwokerto. Data analysis in the study included correlation, paird t-test, and independent t-test. The findings of the study show that the levels of knowledge and self care in mothers with primipara post partum were significantly different between control and experimental group as well as before and after intervention in experimental group (p less than 0.001).FCMC: discharge planning and home care could enhance the level of knowledge and self care in mothers with primipara post partum.